Enhancement of antitumor activity of harringtonine in human leukemia-60 cells in vitro by verapamil - Wang Lei; Zhang Hong-Qing; Wang Rui-Hong; He Nong-Gao; Xue Shao-Bai (Acta Pharmacologica Sinica, 2016)
The effect of harringtonine (Har) alone and in combination with verapamil (Ver) on the proliferation of human leukemia-60 (HL-60) cells in vitro were studied. IC50 of Har alone to the cells was about 49 ng.ml-1 which was reduced to its 1/3.3 and 1/4.5 when used with Ver 1 and 2 micrograms.ml-1, respectively. In colony forming test, the survival fraction of the HL-60 cells treated with Har 15 and 30 ng.ml-1 plus Ver 2 micrograms.ml-1 was reduced to 1/3.3 and 1/8 of the cells as when treated with Har alone, respectively. The results suggested that Ver enhanced the antitumor activity of Har in vitro and may used as an enhancer of Har in vivo.